The Effect of Baby Massage on Language Development Disorder (Speech Delay) - Marta Pastari; Syokumawena Syokumawena (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is directed to answer the following problems; Is there an Influence of Baby Massage on Language Development Disorders (Speech Delay). This study uses a pre-experimental design, because there are variables outside the independent variables that can affect the dependent variable. The research design used was Two Group Pre-Posttest Design (Nuryadi, et al, 2017). The treatment given is; 1) Group I = given Speech Therapy without Oromotor (Speech Therapy Massage) = 16 people; 2) Group II = given Speech Therapy with Oromotor (Speech Therapy Massage) = 16 people. Therapy was given for 3 consecutive months. This research activity was carried out in two places, namely NU_Kids Integrated Therapy 1 and 2. The results of the analysis showed that; 1) Most of the children who were given treatment only with speech therapy (Group I) had severe autism, namely 11 people (68.8%) then most of the children who were given a combination treatment, namely Speech Therapy and Oromotor (Speech Therapy Massage) ) (Group II) also experienced severe autism, namely 9 people (56.3%). This shows that children with severe autism really need speech therapy to deal with communication disorders that can be detected through speech delays (Speech Delay); 2) The results of the different language development test using the Wilcoxon Signed Ranks Test (asymp sig 2-Tailed) showed that in Group I; only children with severe autism category have differences in language development in pre and post treatment; Then in Group II; children with moderate and severe autism categories have differences in language development in pre and post treatment; 3) The ANOVA test results obtained that the F table value from the calculation is 4.17, which is, the calculated F value is in the rejection area (F arithmetic > F table), then H0 is rejected and H1 is accepted. The conclusion is that the speaking ability of the two groups is significantly different, so that it is found that there is "The Effect of Baby Massage on Language Development Disorders (Speech Delay)”.